Interpretation of Regulatory and Legal Acts in Contemporary Contexts: Foreign Experience, Comparative Perspectives, and Pathways for Regulatory Reform - Yevhen Leheza; Oleksandr Kurakin; Olha Shapovalova; Kateryna Sokh; Artur Makarov (Islamic Research Publiser, 2026)
This article examines the theoretical and legal foundations of interpreting regulatory and legal acts in contemporary contexts, with particular emphasis on integrating foreign experience into the Ukrainian legal system. The study aims to identify methodological gaps in domestic interpretative practice and to formulate pathways for regulatory reform aligned with European standards. Employing a comparative legal methodology, the research analyses interpretative approaches across continental systems (Germany and France) and Anglo-Saxon systems (Great Britain and the United States), as well as the jurisprudence of supranational judicial institutions, notably the Court of Justice of the European Union and the European Court of Human Rights. The analysis combines doctrinal examination, case-law review, and systemic legal analysis. The findings demonstrate that the continental tradition ensures coherence, systematicity, and legal certainty, whereas the precedent-based model emphasises flexibility, judicial creativity, and practical justice. In contrast, interpretative practice in Ukraine remains predominantly formalistic, lacks methodological integration, and is insufficiently responsive to the dynamics of European integration. The study substantiates the feasibility of combining domestic legal traditions with advanced European interpretative methods, particularly teleological, systemic, and evolutionary approaches oriented toward the rule of law and human rights protection. It further argues for strengthening the Supreme Court's role in ensuring uniform judicial practice and fostering doctrinal development. The article contributes to comparative legal scholarship by proposing a structured model of interpretative reform that bridges continental and precedent-based traditions. Its practical significance lies in enhancing the quality of law enforcement, promoting harmonisation with European legal standards, and fostering a modern culture of legal interpretation responsive to contemporary regulatory challenges.